MATHEMATICAL REPRESENTATION OF CHILDREN'S PLAY PROCESS THROUGH PUZZLE GAMES AT KB AL MUTTAQIN WEDUNG DEMAK - Sa’adah, Zumrotus (Schola, 2023)
This study aims to find out the improvement of mathematical connection skills in early childhood through snakes and ladders game activities. This study is backgrounded by low mathematical ability, namely cognitive development in children aged 5 - 6 years. This is allegedly due to the lack of interesting media that teachers use in learning. Many teachers pay less attention to the use of real-world contexts, particularly in cognitive development programs. Teachers tend to use more worksheets and the games used are also less attractive to children. This study uses case study method, data collection technique using observation, interview, and documentation. Based on the results of the study, it can be concluded that through the game Snakes and Ladders can improve the ability of mathematical connections in cognitive development in early childhood, especially in children aged 5 - 6 years.